NMFPP-coated NVPOF composite material and preparation and application thereof
By using a non-hydrothermal low-temperature precipitation process to coat NVPOF on the surface of NMFPP positive electrode material and performing thermal modification treatment, the problem of insufficient air stability and fast charging performance of NMFPP materials is solved, and its electrochemical performance and application prospects are significantly improved.
Patent Information
- Application Number
- CN202510068905.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-16
AI Technical Summary
NMFPP positive electrode material has problems such as poor air stability, low conductivity and low energy density at high magnification, which limits its application in sodium ion batteries.
The surface of NMFPP active material is coated with NVPOF by a non-hydrogenic low-temperature precipitation process, and the interface is reconstructed through thermal modification treatment to improve the air stability and fast charging performance of the material.
It significantly improves the air stability and fast charging performance of the material, enhances the electrochemical performance, and enables NMFPP positive electrode material to show a broader application prospect in sodium ion batteries.
Smart Images

Figure CN119852369A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular to the field of positive electrode materials for sodium ion batteries. Technical Background
[0002] With the development of science and technology and the improvement of human living standards, people's demand for energy is growing rapidly, and environmental problems are becoming increasingly prominent, especially the consumption of fossil energy and greenhouse gas emissions. In this context, the research and development of environmentally friendly clean energy and energy storage systems such as batteries is particularly important. The success of lithium-ion batteries in recent years has led to a significant increase in the consumption of lithium resources. The fluctuating price of lithium resources, uneven resource distribution and poor low-temperature adaptability are not conducive to their further development. In this context, sodium-ion batteries (SIBs) have gradually become a research hotspot and a potential candidate for the next generation of battery technology due to their low cost, abundant resources and superior low-temperature performance.
[0003] In recent years, researchers have studied many sodium-ion battery cathode materials, such as layered oxides, polyanions, and Prussian blue. Among them, polyanion cathode materials have stable three-dimensional structures, wide voltage platforms, and high thermal stability, making them particularly suitable for energy storage. The superior structural stability and rate performance of polyanion cathode materials have attracted the attention of many researchers, among which sodium iron pyrophosphate (manganese) phosphate cathode material Na y Mn x Fe 3-x P2O7(PO4)2 / C, 0≤x<2.5, 3.8≤y<4.1 (NMFPP) not only has the advantages of polyanionic materials, but also has low cost, making it a very promising cathode material for sodium ion batteries.
[0004] However, NMFPP has problems such as weak air stability, low electrical conductivity and low energy density at high rates (see Li X, Dai S, Chen Q, et al. Understanding Air Sensitivity and Deterioration Mechanism of Na4Fe3(PO4)2P2O7 Cathode for Na-Ion Battery[J]. Journal of Materials Chemistry A, 2024, 12(43): 29726-29734. and Yang Y, Wang Z, Du C, et al. Decoupling the air sensitivity of Na-layered oxides[J]. Science, 2024, 385(6710): 744-752.), which limits its further development.
[0005] In addition, the Chinese patent document with publication number CN 114068938A discloses a method for preparing a composite material of sodium pyrophosphate coated with sodium ferric phosphate and vanadium fluoride phosphate, which obtains a sodium ferric pyrophosphate precursor by a first hydrothermal reaction, and then performs a second hydrothermal encapsulation with a second sodium source, a vanadium source, a second phosphorus source, a fluorine source and a second complexing agent, followed by heat treatment. This process method requires the use of a hydrothermal treatment process, and it is difficult to reconstruct a new fusion interface between the bulk phase and the interface of the prepared material. The air resistance stability and high-rate long cycle performance of the material need to be further improved. Summary of the invention
[0006] In view of the problems that it is difficult to construct a uniform surface and a fusion interface of the NMFPP@NVPOF composite material, and the material's air stability and high-rate performance are not ideal, the first purpose of the present invention is to provide a method for preparing an NMFPP@NVPOF composite material, aiming to prepare a composite material with a suitable reconstruction interface (coherent interface) and excellent air stability and fast charging performance.
[0007] The second object of the present invention is to provide a NMFPP@NVPOF composite material obtained by the preparation method and its application in sodium ion batteries.
[0008] The third object of the present invention is to provide a sodium ion battery comprising the NMFPP@NVPOF composite material and a positive electrode and a positive electrode material thereof.
[0009] A method for preparing a NMFPP@NVPOF composite material, comprising: subjecting VOPO4, a sodium source and a fluorine source to a precipitation reaction on the surface of an NMFPP active material, coating the NMFPP surface with NVPOF, and then subjecting the NMFPP surface to a thermal modification treatment to obtain the NMFPP@NVPOF composite material;
[0010] The chemical formula of NMFPP is Na y Mn x Fe 3-x P2O7(PO4)2,0≤x<2.5,3.8≤y<4.1;
[0011] The expression of NVPOF is Na3V2(PO4)2O 3-z F z ,1≤z≤3.
[0012] Different from the conventional hydrothermal encapsulation process, the present invention innovatively provides a process idea for forming NVPOF based on non-hydrothermal low-temperature precipitation. It innovatively directly uses NMFPP active material as the substrate, and utilizes its physical and chemical characteristics such as residual alkali and residual sodium on the surface and the good adaptability of NVPOF to induce the surface precipitation of VOPO4, sodium source and fluorine source, and further cooperates with subsequent thermal modification treatment, so as to induce interface reconstruction and induce gradient exudation of metal and non-metal. The research of the present invention shows that the preparation method can significantly improve the air stability of the material, and in addition, it can also improve the fast charging performance of the material.
[0013] The research of the present invention shows that directly using VOPO4 as a phosphorus and vanadium source, combined with the deposition induction mechanism of the surface physicochemical characteristics of the NMFPP active material described in the present invention, can unexpectedly induce the uniform deposition of NVPOF on the surface of NMFPP. In addition, it is also beneficial to the subsequent reconstruction of the fusion interface, and is beneficial to the air stability and fast charging performance of the material.
[0014] In the present invention, the VOPO4 can be selected from commercial products or prepared based on conventional means, for example, it can be obtained by pre-reaction of a phosphorus source, a vanadium source, and a reducing agent.
[0015] In the present invention, the sodium source is at least one of sodium fluoride, sodium carbonate, sodium bicarbonate, sodium hydroxide and sodium citrate.
[0016] The fluorine source is at least one of sodium fluoride, ammonium fluoride and polyvinylidene fluoride.
[0017] The present invention shows that the physicochemical characteristics of the surface of NMFPP active material can unexpectedly induce the surface precipitation of NVPOF by directly using it as a deposition substrate, thereby facilitating the construction of a uniform, stable composite material that is conducive to the formation of a reconstructed interface. In the present invention, the NMFPP can be a commercial active material or can be prepared based on existing means.
[0018] In the present invention, NVPOF accounts for 1 to 10% by weight of NMFPP; further, it may be 3 to 8%, and further, it may be 4 to 6%.
[0019] In the present invention, the solvent of the precipitation reaction is at least one of water, ethanol, isopropanol, and ethylene glycol; preferably, it is a mixed solvent containing water; for example, it can be a water-alcohol mixed solvent, and the alcohol includes at least one of ethanol, isopropanol, and ethylene glycol. In the mixed solvent, the volume ratio of water to alcohol is, for example, 1 to 5:1, and can further be 2 to 3:1. Studies have shown that carrying out the precipitation reaction under the preferred conditions helps to further optimize the homogenized coating of the surface layer based on the induction effect of the core, and further facilitates the preparation of a composite material with high stability of the coherent interface, excellent fast charging, and air resistance stability.
[0020] In the present invention, a thermal modification treatment is further performed under the non-hydrothermal low-temperature precipitation process, so that the dissolution interface can be reconstructed, which helps to improve the air stability and fast charging performance of the material.
[0021] In the present invention, the atmosphere for heat treatment is a protective atmosphere.
[0022] In the present invention, the temperature of the thermal modification treatment is 300 to 700°C, and can further be 450 to 550°C;
[0023] Preferably, the thermal modification treatment time is 1 to 12 hours, and further can be 3 to 5 hours.
[0024] The present invention also provides a NMFPP@NVPOF composite material prepared by the preparation method, which has a core-shell structure, wherein the core comprises NMFPP, the shell is NVPOF, and a reconstructed fusion interface exists between the core and the shell.
[0025] The present invention also provides an application of the NMFPP@NVPOF composite material, which is used as a positive electrode active material for preparing a sodium ion battery.
[0026] The present invention also provides a sodium ion battery positive electrode, comprising a current collector and a positive electrode material composited on the surface thereof, wherein the positive electrode material comprises a positive electrode active material, wherein the positive electrode active material comprises the NMFPP@NVPOF composite material prepared by the present invention.
[0027] The present invention also provides a sodium ion battery positive electrode, comprising the positive electrode described in the present invention.
[0028] In the present invention, the NMFPP@NVPOF composite material of the present invention can be used as a positive electrode active material based on known raw materials and methods to prepare the required sodium ion battery. In addition to the NMFPP@NVPOF composite material of the present invention, the other components, parts and structural relationships of the sodium ion battery can be conventional.
[0029] Beneficial effects:
[0030] Different from the existing conventional hydrothermal encapsulation methods, the present invention innovatively utilizes NMFPP active material as a substrate, and takes advantage of its surface physicochemical characteristics, as well as the compatibility between the physicochemical characteristics and NVOPF, and innovatively subjects VOPO4, sodium source and F source to a non-solvothermal low-temperature precipitation reaction under the surface induction of NMFPP, thereby forming a uniform precipitation interface. Further combined with subsequent thermal modification treatment, the fusion interface can be reconstructed to improve the gradient extravasation effect of the components, thereby significantly improving the air stability and fast charging performance of the prepared material.
[0031] The present invention also shows that the processing conditions, especially the solvent in the precipitation stage, can help further optimize the homogenized coating effect of the surface layer, and facilitate the coordinated construction of a coherent interface, optimizing the fast filling and air resistance stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the XRD spectrum of the 95% Na4Fe3(PO4)2P2O7 / 5% NVPOF / C-24h positive electrode material prepared in Example 1.
[0033] Figure 2 This is a FT-IR comparison chart of 95% Na4Fe3(PO4)2P2O7 / 5% NVPOF / C-24h and Na4Fe3(PO4)2P2O7 / C positive electrode materials prepared in Example 1.
[0034] Figure 3 This is a comparison chart of the electrochemical properties of the 95% Na4Fe3(PO4)2P2O7 / 5% NVPOF / C-24h positive electrode material and the Na4Fe3(PO4)2P2O7 / C positive electrode material prepared in Example 1.
[0035] Figure 4 This is the SEM-EDS image of the 95% Na4Fe3(PO4)2P2O7 / 5% NVPOF / C-24h positive electrode material prepared in Example 1.
[0036] Figure 5 This is a SEM comparison picture of the 95% Na4Fe3(PO4)2P2O7 / 5% NVPOF / C-7day and NFPP / C-7day positive electrode materials prepared in Example 1.
[0037] Figure 6 This is the XRD spectrum of the 92% Na4Mn2Fe(PO4)2P2O7 / 8% NVPOF / C positive electrode material prepared in Example 2.
[0038] Figure 7This is a comparison chart of the electrochemical properties of the 92% Na4Mn2Fe(PO4)2P2O7 / 8% NVPOF / C positive electrode material prepared in Example 2 and the Na4Mn2Fe(PO4)2P2O7 / C positive electrode material in Comparative Example 2.
[0039] Figure 8 This is the SEM image of the 92% Na4Mn2Fe(PO4)2P2O7 / 8% NVPOF / C positive electrode material prepared in Example 2.
[0040] Fig. 9 This is the electrochemical performance diagram of the 97% Na4Fe3(PO4)2P2O7 / 3% NVPOF / C positive electrode material prepared in Example 3.
[0041] Fig.10 This is the XRD spectrum of the Na4Fe3(PO4)2P2O7C-24h positive electrode material prepared in Comparative Example 1.
[0042] Fig.11 This is a FT-IR comparison chart of the Na4Fe3(PO4)2P2O7C-24h positive electrode material and the Na4Fe3(PO4)2P2O7 / C positive electrode material prepared in Comparative Example 1.
[0043] Fig.12 This is the electrochemical performance diagram of the Na4Fe3(PO4)2P2O7C-24h positive electrode material prepared in Comparative Example 1.
[0044] Fig.13 This is the SEM image of the Na4Fe3(PO4)2P2O7C-24h positive electrode material prepared in Comparative Example 1.
[0045] Fig.14 This is the SEM image of the Na4Mn2Fe(PO4)2P2O7 / C positive electrode material prepared in Comparative Example 2.
[0046] Fig.15 This is the electrochemical performance diagram of the 95% NFPP / C+5% NVPOF mixture prepared in Comparative Example 3.
[0047] Fig.16 This is the SEM image of the 95% NFPP / C+5% NVPOF mixture prepared in Comparative Example 3.
[0048] Fig.17 This is the electrochemical performance diagram of the 92% NMFPP / C+8% NVPOF mixture prepared in Comparative Example 4.
[0049] Fig.18 This is the electrochemical performance diagram of the positive electrode material prepared in Comparative Example 5.
[0050] Table 1 is a comparison table of the electrochemical properties of the positive electrode material prepared in Comparative Example 6 and the positive electrode materials prepared in Example 1 and Example 4. DETAILED DESCRIPTION
[0051] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner in conjunction with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.
[0052] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0053] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.
[0054] The present invention utilizes a method for coating sodium (manganese) iron pyrophosphate positive electrode material by low-temperature liquid phase precipitation of sodium vanadyl fluorophosphate, uniformly coats a layer of structurally stable fast ion conductor on the surface of the NMFPP positive electrode material, and induces surface reconstruction to obtain a composite material with the same system and different components, with NMFPP / C as the core and NVPOF as the shell. The disadvantage of poor air stability of the NMFPP positive electrode material is effectively improved without reducing the energy density, and the electrochemical performance of the material is greatly improved, so that the NMFPP positive electrode material shows a broader prospect.
[0055] The steps of the method are, for example, to pre-react a vanadium source and a phosphorus source with a reducing agent at a certain temperature for a certain period of time to obtain a blue slurry containing vanadium and phosphorus; to add a certain amount of Na y Mn x Fe 3-x P2O7(PO4)2 / C, 0≤x<2.5, 3.8≤y<4.1(NMFPP / C) positive electrode material, then add sodium source and fluorine source and adjust the temperature and stir the reaction for a period of time, then adjust the pH so that the vanadium phosphorus slurry is Na3V2(PO4)2O 3-z F z ,1≤z≤3(NVPOF) precipitates are uniformly coated on the surface of NMFPP / C material; after filtration and washing and drying in a vacuum oven, heat treatment is performed in an inert atmosphere to induce surface reconstruction, forming a coherent interface between NMFPP and NVPOF particles, and obtaining a composite material with the same system and different components with NMFPP / C as the core and NVPOF as the shell, and a fast ion conductor with stable structure is uniformly coated on the surface of NMFPP material.
[0056] As a preferred solution, the solvent of the solution is at least one of water, ethanol, isopropanol, and ethylene glycol, and the solvent can ensure that the NMFPP / C positive electrode material is well dispersed;
[0057] As a preferred solution, the phosphorus source is at least one of phosphoric acid, ammonium dihydrogen phosphate and diammonium hydrogen phosphate. In the present invention, the phosphorus source can provide a large amount of phosphate ions to combine with the vanadium ions in the vanadium source.
[0058] As a preferred solution, the vanadium source is at least one of vanadium pentoxide, vanadium dioxide, ammonium metavanadate, and sodium vanadate;
[0059] As a preferred solution, the reducing agent is at least one of ascorbic acid, oxalic acid, formic acid and lactic acid.
[0060] As a preferred solution, the sodium source is at least one of sodium fluoride, sodium carbonate, sodium bicarbonate, sodium hydroxide and sodium citrate.
[0061] As a preferred solution, the fluorine source is at least one of sodium fluoride, ammonium fluoride, and polyvinylidene fluoride.
[0062] As a preferred solution, the reduction temperature is 40-90°C and the reduction time is 0.1-2h.
[0063] The coating reaction temperature is 60-90°C, and the adjusted pH is 6-9.
[0064] As a preferred scheme, the molar ratio of the added sodium element, vanadium element, phosphorus element and fluorine element is (2-5): (1.5-3): (2-4): (1-5), and more preferably (2-4): (2-2.5): (2.5-3.5): (2-4).
[0065] As a preferred solution, the molar ratio of the added vanadium source to the reducing agent is (1:4) to (1:
[0066] 1), and more preferably (1:3) to (1:1.5).
[0067] As a preferred solution, the mass ratio of the theoretically generated NVPOF to the added NMFPP / C is (1:99) to (1:3), and more preferably (1:19) to (3:17).
[0068] As a preferred solution, the inert atmosphere is at least one of argon, nitrogen, and hydrogen and argon.
[0069] As a preferred solution, the heat treatment temperature is 300-700°C, the heating rate is 1-10°C / min, and the holding time is 1-12h; more preferably, the temperature is 450-650°C, the heating rate is 2-5°C, and the holding time is 4-8h. If the sintering temperature is too high, it will easily lead to the formation of impurities, and if the sintering temperature is too low, the interface interaction between NVPOF and the matrix material will be low.
[0070] A more specific method for modifying a positive electrode material by using sodium vanadium fluorophosphate to coat sodium (manganese) iron pyrophosphate by low-temperature liquid phase precipitation of the present invention specifically comprises the following steps:
[0071] 1) Add a phosphorus source, a vanadium source and a reducing agent into a certain amount of deionized water and carry out a reduction reaction at a certain temperature for 0.1-2 hours, maintaining the molar ratio of the elemental vanadium in the vanadium source added to the solution: the elemental phosphorus in the phosphorus source at (1:3) to (1:1), and the molar ratio of the elemental vanadium in the vanadium source added to the reducing agent at (1:4) to (1:1).
[0072] 2) Adding a certain amount of NMFPP / C positive electrode material and a sodium source and a fluorine source to the solution after the reduction reaction in step 1) and adjusting the temperature and pH to obtain a composite material in which NVPOF is uniformly coated with NMFPP / C, maintaining the molar ratio of the sodium element in the added sodium source, the vanadium element in the vanadium source, the phosphorus element in the phosphorus source, and the fluorine element in the fluorine source at (2-5): (1.5-3): (2-4): (1-5), the temperature is 60-90°C, and the pH is 6-9.
[0073] 3) Na3V2(PO4)2O synthesized in liquid phase obtained in step 2) 3-z F z ,1≤z≤3(NVPOF) coated with Na y Mn x Fe 3- x The P2O7(PO4)2 / C, 0≤x<2.5, 3.8≤y<4.1 (NMFPP) material is filtered, washed, and dried in a vacuum oven to obtain a powder to be sintered.
[0074] 4) The powder of step 3) is heat treated to obtain the NMFPP / NVPOF / C composite positive electrode material. The sintering temperature is 300-700° C. and the holding time is 1-12 hours.
[0075] Example 1
[0076] 1) After 0.065 mol of 85% mass fraction phosphoric acid was diluted with deionized water in a flask, 0.026 mol of vanadium pentoxide and 0.078 mol of dihydrated oxalic acid were added while stirring. The molar ratio of phosphorus to vanadium in the slurry was 1.25:1, and the molar ratio of vanadium to dihydrated oxalic acid was 2:3. At the same time, the slurry was heated to 70°C and stirred for 1 hour. Finally, the slurry turned dark blue.
[0077] 2) Add 204.516g Na4Fe3(PO4)2P2O7 / C (carbon content between 1.5% and 3%) (NFPP / C) to the vanadium-phosphorus slurry obtained in step 1) so that the mass ratio of the theoretically generated NVPOF:NFPP / C is 5%:95%, and then add 0.104mol NaF after stirring for a period of time, heat to 90°C and stir for 20min, then adjust the pH to 6 by adding 0.5mol / L NaOH and keep stirring at this temperature for 20min to obtain a composite material in which NVPOF is uniformly coated on the surface of NFPP / C.
[0078] 3) The slurry in step 2) is filtered and washed three times, and the washed precipitate is placed in a vacuum oven at 80° C. and dried to obtain a composite material powder to be sintered.
[0079] 4) Sintering the powder of step 3) in an argon atmosphere at 480° C. for 4 h with a heating rate of 3° C. / min. After sintering, cooling to room temperature can obtain a 95% NFPP / 5% NVPOF / C positive electrode material.
[0080] 5) The powder of step 4) was placed in air with a humidity of 30% for 24 hours to obtain
[0081] 95%NFPP / 5%NVPOF / C-24h positive electrode material.
[0082] like Figure 1 This is the XRD pattern of 95% NFPP / 5% NVPOF / C-24h.
[0083] like Figure 2 The FT-IR spectra of 95% NFPP / 5% NVPOF / C and 95% NFPP / 5% NVPOF / C-24h showed that there was no -1 CO3 detected nearby 2- No Na2CO3 is generated on the surface of the material, and compared with the FT-IR of Comparative Example 2, it has better air stability.
[0084] The 95% NFPP / 5% NVPOF / C and 95% NFPP / 5% NVPOF / C-24h positive electrode materials prepared by the method of Example 1: acetylene black: binder PVDF are mixed in a mass ratio of 7:2:1, and NMP is used as a solvent. The mixed slurry is obtained in a homogenizer. The obtained slurry is coated on an aluminum foil, dried in a vacuum oven at 120°C for 12 hours, and then punched into a disc-shaped electrode piece with a diameter of 12 mm. The electrode piece is assembled into a CR2025 button battery in a pure argon glove box. At 25°C, the charge and discharge cut-off voltage is set to 1.7~4.3V to carry out 0.1C constant current charge and discharge test, 1C long cycle test and different charge and discharge rate tests, such as Figure 3 As shown, the prepared 95% NFPP / 5% NVPOF / C has high capacity, and there is a charge and discharge platform of NVPOF near 3.45V that provides a certain capacity, and has good rate performance and cycle stability. 95% NFPP / 5% NVPOF / C-24h has good air stability while taking into account the electrochemical performance. In addition, the performance of 95% NFPP / 5% NVPOF / C and 95% NFPP / 5% NVPOF / C-24h at different rates, especially the high rate performance, is greatly improved. This is all due to the formation of coherent interfaces that improve the electrochemical activity of the material.
[0085] like Figure 4 The SEM-EDS image of 95% NFPP / 5% NVPOF / C-24h shows that the surface of 95% NFPP / 5% NVPOF / C-24h is gully-shaped, and there is no film such as sodium carbonate coated on the secondary sphere of the material. The V and F elements are evenly distributed on the surface of the secondary sphere. The surface of the material is obviously rough, indicating that there is a surface reconstruction phenomenon during the liquid phase coating process, which is also consistent with the SEM of Comparative Example 1. Fig.13 , SEM of Comparative Example 3 Fig.16 Create a contrast.
[0086] like Figure 5 The SEM images of 95% NFPP / 5% NVPOF / C-7day and NFPP / C-7day show that the former still presents a morphology consistent with the material exposed to the air, while the latter contains a large amount of needle-like substances due to the side reaction with the air. Combined with the electrochemical performance comparison with Comparative Example 1, the air stability of the material is greatly improved.
[0087] Example 2
[0088] 1) After 0.065 mol of 85% mass fraction phosphoric acid was diluted with ethanol in a flask, 0.026 mol of vanadium pentoxide and 0.078 mol of dihydrated oxalic acid were added while stirring. The molar ratio of phosphorus to vanadium in the slurry was 1.25:1, and the molar ratio of vanadium to dihydrated oxalic acid was 2:3. At the same time, the slurry was heated to 70°C and stirred for 1 hour. Finally, the slurry turned dark blue.
[0089] 2) Add 123.786gNa4Mn2Fe(PO4)2P2O7 / C(NM2FPP / C) to the vanadium-phosphorus slurry obtained in step 1) so that the mass ratio of the theoretically generated NVPOF:NMFPP / C is 8%:92%, and then add 0.104molNaF after stirring for a period of time, keep stirring at 90°C for 20min, and then adjust the pH to 6.5 by adding 0.5mol / L NaOH and keep stirring at this temperature for 20min to obtain a composite material in which NVPOF is uniformly coated on the surface of NMFPP / C.
[0090] 3) The slurry in step 2) is filtered and washed three times, and the washed precipitate is placed in a vacuum oven at 70° C. and dried to obtain a composite material powder to be sintered.
[0091] 4) Pre-sinter the powder of step 3) in an argon atmosphere at 500°C for 4 hours with a heating rate of 3°C / min. After sintering, cool to room temperature to obtain a 92% NM2FPP / 8% NVPOF / C positive electrode material.
[0092] like Figure 6 This is the XRD pattern of 92% NM2FPP / 8% NVPOF / C.
[0093] The 92% NM2FPP / 8% NVPOF / C positive electrode material prepared by the method of Example 2: acetylene black: binder PVDF are mixed in a mass ratio of 7:2:1, and NMP is used as a solvent. The mixed slurry is obtained in a homogenizer. The obtained slurry is coated on an aluminum foil, dried in a vacuum oven at 120°C for 12 hours, and then punched into a disc-shaped electrode piece with a diameter of 12 mm. The electrode piece is assembled into a CR2025 button battery in a pure argon glove box. At 25°C, the charge and discharge cut-off voltage is set to 1.7~4.3V to carry out 0.1C constant current charge and discharge test, 1C long cycle test and different charge and discharge rate tests, such as Figure 7 As shown, it can be clearly seen that the 92% NM2FPP / 8% NVPOF / C positive electrode has a charge and discharge platform at around 3.4V, and the electrochemical performance is significantly improved in capacity, cycle performance and rate performance compared to the unmodified NM2FPP / C.
[0094] like Figure 8The SEM image of 92% NM2FPP / 8% NVPOF / C shows that Fig.14 Compared with the SEM image of comparative example 2, it can be seen that there are grooves, i.e. small holes, on the surface of the material after liquid phase coating, which is not as smooth as that of comparative example 2, indicating that there is surface reconstruction during the liquid phase coating process, which is in line with the expected results.
[0095] Example 3
[0096] 1) 0.065 mol of 85% mass fraction phosphoric acid was diluted with a 1:1 mixed solvent of deionized water and anhydrous ethanol in a flask, and then 0.026 mol of vanadium pentoxide and 0.052 mol of dihydrated oxalic acid were added while stirring. The molar ratio of phosphorus to vanadium in the slurry was 1.25:1, and the molar ratio of vanadium to dihydrated oxalic acid was 1:1. At the same time, the slurry was heated to 70°C and stirred for 1 hour. Finally, the slurry turned dark blue.
[0097] 2) Add 348.04 g Na4Fe3(PO4)2P2O7C (carbon content between 1.5% and 3%) (NFPP / C) to the vanadium-phosphorus slurry obtained in step 1) so that the mass ratio of the theoretically generated NVPOF:NFPP / C is 3%:97%. After stirring for a period of time, add 0.078 mol NaF, maintain the temperature at 70°C and stir for 20 minutes to obtain a composite material in which NVPOF is uniformly coated on the surface of NFPP / C.
[0098] 3) The slurry in step 2) is filtered and washed three times, and the washed precipitate is placed in a vacuum oven at 80° C. and dried to obtain a composite material powder to be sintered.
[0099] 4) Sintering the powder of step 3) in an argon atmosphere at 500° C. for 4 h with a heating rate of 3° C. / min. After sintering, cooling to room temperature can obtain a 97% NFPP / 3% NVPOF / C positive electrode material.
[0100] The 97% NFPP / 3% NVPOF / C positive electrode material prepared by the method of Example 3: acetylene black: binder PVDF are mixed in a mass ratio of 7:2:1, and NMP is used as a solvent. The mixed slurry is obtained in a homogenizer. The obtained slurry is coated on an aluminum foil sheet, dried in a vacuum oven at 120°C for 12 hours, and then punched into a disc-shaped electrode piece with a diameter of 12 mm. The electrode piece is assembled into a CR2025 button battery in a pure argon glove box. At 25°C, the charge and discharge cut-off voltage is set to 1.7~4.3V to carry out 0.1C constant current charge and discharge test, 1C long cycle test and different charge and discharge rate tests, such as Fig. 9As shown, it can be clearly seen that the overall curve of the 97% NFPP / 3% NVPOF / C positive electrode is almost consistent with the embodiment, with better rate performance and capacity and the best cycle performance. This is because the amount of coated NVPOF is moderate, and NFPP / C can be better dispersed in anhydrous ethanol than in water, which is more conducive to uniform coating of NVPOF, and thus conducive to inducing interface reconstruction, effectively activating sodium embedded sites, and the appropriate amount of coating promotes cycle stability, which is the preferred solution.
[0101] Example 4
[0102] Compared with Example 1, the only difference is that ethanol is added to the precipitation reaction system in step 2, wherein the volume ratio of water to ethanol in the system is 2:1; the total amount of solvent and other operations and parameters are the same as those in Example 1
[0103] Comparative Example 1
[0104] The only difference between this comparative example and Example 1 is that the Na4Fe3(PO4)2P2O7 / C (NFPP / C) is not modified by NVPOF coating, and the NFPP / C is exposed to air with a humidity of 30% for 24 hours to obtain NFPP / C-24h.
[0105] The XRD peak intensity of NFPP / C-24h was significantly weakened, and the (004) and (222) peaks were split. This was due to the poor air stability of NFPP / C, which resulted in the Na3 sites in the exposed material being + Changes caused by escaping from the lattice ( Fig.10 ). The FT-IR results of NFPP / C-24h are as follows Fig.11 As shown, at 1480cm -1 CO3 detected nearby 2- The characteristic peaks of the material prove that Na2CO3 is generated on the surface of the material. The electrochemical performance of the material is greatly affected. The first cycle efficiency of 0.1C is 107.58%, and the charging platform near 2.7V belonging to the Na3 site for de-Na+ disappears. The material cycle performance and discharge specific capacity have decreased significantly (see Fig.12 ).
[0106] The SEM spectrum of the NFPP / C-24h positive electrode material prepared in Comparative Example 1 is as follows: Fig.13 As shown in the figure, the surface of the secondary sphere particles is very smooth, which is caused by the presence of Na2CO3 film on the surface.
[0107] Comparative Example 2
[0108] The only difference between this comparative example and Example 2 is that NVPOF is not used for coating, and Na4Mn2Fe(PO4)2P2O7 / C (NM2FPP / C) is prepared.
[0109] The electrochemical data of the Na4Mn2Fe(PO4)2P2O7 / C (NM2FPP / C) cathode material prepared in Comparative Example 2 are compared with the electrochemical data prepared in Example 2. Figure 6 As shown in the SEM images Fig.14 shown.
[0110] The results show that the electrochemical performance of the positive electrode material is reduced when NM2FPP / C is not coated with NVPOF.
[0111] Comparative Example 3
[0112] The only difference between this comparative example and Example 1 is that Na4Fe3(PO4)2P2O7 / C(NFPP / C) is not added to the pre-reacted vanadium oxide slurry for NVPOF coating modification. Instead, Na4Fe3(PO4)2P2O7 / C(NFPP / C) and NVPOF / C are physically mixed and sintered under the same conditions to obtain a 95% NFPP / C + 5% NVPOF mixture.
[0113] The electrochemical data of the 95% NFPP / C + 5% NVPOF mixture prepared in Comparative Example 3 are compared with the electrochemical data of the bare NFPP / C material. Fig.15 As shown; the SEM image of 95% NFPP / C+5% NVPOF mixture is as follows Fig.16 shown.
[0114] It can be seen that there is an obvious charge and discharge platform of NVPOF / C at around 3.4V, indicating that simple mixed sintering of NFPP / C and NVPOF / C cannot achieve the excellent effect of the same system with different components.
[0115] Comparative Example 4
[0116] The only difference between this comparative example and Example 2 is that Na4Mn2Fe(PO4)2P2O7 / C(NM2FPP / C) is not added to the pre-reacted vanadium oxide slurry for NVPOF coating modification, but NVPOF / C is first prepared using the process conditions; then Na4Mn2Fe(PO4)2P2O7 / C(NM2FPP / C) and NVPOF / C are physically mixed and sintered under the same conditions to obtain a 92% NM2FPP / 8% NVPOF / C mixture.
[0117] The electrochemical data of the 92% NM2FPP / 8% NVPOF / C mixed material prepared in Comparative Example 4 are compared with the electrochemical data of the NFPP / C bare material. Fig.17 shown.
[0118] It can be seen that there is an obvious charging and discharging platform of NVPOF / C at around 3.4V, indicating that the simple mixed sintering of NM2FPP / C and NVPOF / C cannot achieve the excellent effect of the same system with different components.
[0119] Comparative Example 5
[0120] Compared with Example 2, the only difference is that the treatment of step 1 is not performed, but the components such as the phosphorus source and vanadium source in step 1 are directly added to the precipitation system of step 2 for co-precipitation. Other operations and parameters are the same as in Example 1.
[0121] Its electrochemical curve is as follows Fig.18 As shown, compared with Example 2, there is no obvious electrochemical platform at around 2.5 V, which is due to the uneven coating and poor surface reconstruction effect of subsequent heat treatment.
[0122] Comparative Example 6
[0123] Compared with Example 1, the only difference is that in step 2, no coprecipitation treatment is performed, but the mixed system is hydrothermally reacted at a temperature of 130-140° C. to obtain the composite material. Other operations and parameters are the same as in Example 1.
[0124] The electrochemical performance of each case is shown in Table 1
[0125] Table 1
[0126]
[0127] It can be seen from Example 1 that by adopting the low-temperature precipitation process described in the present invention, better electrochemical performance and air resistance stability can be obtained. In particular, excellent fast charging performance can be obtained. In addition, studies have shown that carrying out the low-temperature precipitation treatment in a water-alcohol system can further optimize the fast charging and air resistance stability of the prepared material.
Claims
1. A method for preparing a NMFPP@NVPOF composite material, characterized in that: The VOPO4, sodium source and fluorine source are precipitated on the surface of the NMFPP active material, NVPOF is coated on the surface of the NMFPP, and then the NMFPP@NVPOF composite material is prepared by thermal modification. The chemical formula of NMFPP is Na y Mn x Fe 3-x P2O7(PO4)2,0≤x<2.5,3.8≤y<4.1; The expression of NVPOF is Na3V2(PO4)2O 3-z F z ,1≤z≤3.
2. The method for preparing the NMFPP@NVPOF composite material according to claim 1, characterized in that: The VOPO4 is obtained by pre-reaction of a phosphorus source, a vanadium source and a reducing agent.
3. The method for preparing the NMFPP@NVPOF composite material according to claim 1, characterized in that: The sodium source is at least one of sodium fluoride, sodium carbonate, sodium bicarbonate, sodium hydroxide and sodium citrate. The fluorine source is at least one of sodium fluoride, ammonium fluoride and polyvinylidene fluoride.
4. The method for preparing the NMFPP@NVPOF composite material according to claim 1, characterized in that: The NVPOF is 1-10% of the weight of the NMFPP.
5. The method for preparing the NMFPP@NVPOF composite material according to claim 1, characterized in that: The solvent for the precipitation reaction is at least one of water, ethanol, isopropanol and ethylene glycol; preferably a mixed solvent containing water.
6. The method for preparing the NMFPP@NVPOF composite material according to claim 1, characterized in that: The temperature of thermal modification treatment is 300-700°C; Preferably, the thermal modification treatment time is 1 to 12 hours.
7. A NMFPP@NVPOF composite material obtained by the preparation method according to any one of claims 1 to 6, characterized in that: It has a core-shell structure, wherein the core includes NMFPP, the shell is NVPOF, and there is a reconstructed fusion interface between the core and the shell.
8. An application of the NMFPP@NVPOF composite material according to claim 7, characterized in that: It is used as positive electrode active material to prepare sodium ion batteries.
9. A positive electrode for a sodium ion battery, comprising a current collector and a positive electrode material composited on the surface thereof, wherein the positive electrode material comprises a positive electrode active material, wherein: The positive electrode active material comprises the NMFPP@NVPOF composite material prepared by the preparation method according to any one of claims 1 to 6.
10. A sodium ion battery positive electrode, characterized in that: The positive electrode according to claim 9 is included.
Citation Information
Patent Citations
Preparation method and application of network structure nano NaVPO4F / C composite material and application thereof
CN104112858A
Localized superconcentrated electrolytes for stable cycling of electrochemical devices
CN110352528A
Preparation of sodium vanadium fluorophosphate and application of sodium vanadium fluorophosphate in sodium ion battery
CN114933293A
Carbon-coated Na4Fe3 (PO4) 2P2O7 and carbon-coated NaVPO4F as well as preparation and application thereof
CN118183681A
Compositions and methods for manufacturing a cathode for a secondary battery
US20130078521A1